2007
DOI: 10.1093/cvr/cvm015
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the Z-band protein myopalladin gene and idiopathic dilated cardiomyopathy

Abstract: Based on genetic, histological, and functional evidence, we identified a new gene associated with DCM and observed mutations in 3-4% of cases in a population of European descent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
65
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 26 publications
0
65
0
2
Order By: Relevance
“…As a number of missense mutations in genes encoding for titin and titin-associated proteins have recently been reported to be responsible for DCM, 3,[12][13][14][15][19][20][21][22][23][24][25] we searched in a well-characterized sample of DCM patients for unknown SNPs and/or mutations in the human MYPN and ANKRD1 genes. In order to extend our knowledge on disease-causing mutations in these two proteins expressed in heart tissue, we screened the coding sequences and corresponding intron flanks of the two genes and found two novel non-synonymous mutations in the MYPN gene and only one rare synonymous SNP in the coding region of the ANKRD1 gene.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As a number of missense mutations in genes encoding for titin and titin-associated proteins have recently been reported to be responsible for DCM, 3,[12][13][14][15][19][20][21][22][23][24][25] we searched in a well-characterized sample of DCM patients for unknown SNPs and/or mutations in the human MYPN and ANKRD1 genes. In order to extend our knowledge on disease-causing mutations in these two proteins expressed in heart tissue, we screened the coding sequences and corresponding intron flanks of the two genes and found two novel non-synonymous mutations in the MYPN gene and only one rare synonymous SNP in the coding region of the ANKRD1 gene.…”
Section: Discussionmentioning
confidence: 99%
“…3 The p.R1088H mutation reported in a case of familial DCM is located only one residue, amino-terminally, in the homologous fourth immunoglobulin-like domain as aligned to the corresponding position in the third domain, in which we detected our point mutation p.P961L. 31 Duboscq-Bidot et al 3 have shown that the p.R1088H mutation resulted in a decreased localization of myopalladin to the Z-band area of the left-ventricular cardiac myofibrils, similar to that which we found in the heart tissue from the p.P961L mutation carrier.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations